2003
DOI: 10.1056/nejmoa022600
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD40 Ligand in Acute Coronary Syndromes

Abstract: In patients with unstable coronary artery disease, elevation of soluble CD40 ligand levels indicated an increased risk of cardiovascular events. Elevation of soluble CD40 ligand identifies a subgroup of patients at high risk who are likely to benefit from antiplatelet treatment with abciximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
392
2
12

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 765 publications
(433 citation statements)
references
References 38 publications
24
392
2
12
Order By: Relevance
“…In the latter case, activated platelets expressing or releasing CD40L [22,24] could also interact with CD40 on duct cells, since islet cell suspensions are directly injected into the portal vein. CD40-CD40L interactions at the pancreatic duct cell level could therefore contribute to beta cell damage in Type 1 diabetes and after islet transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, activated platelets expressing or releasing CD40L [22,24] could also interact with CD40 on duct cells, since islet cell suspensions are directly injected into the portal vein. CD40-CD40L interactions at the pancreatic duct cell level could therefore contribute to beta cell damage in Type 1 diabetes and after islet transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The ligand for CD40 (CD40L) is a type II transmembrane protein expressed on stimulated T cells but also on mast cells, basophils and platelets. A soluble form of CD40L is released from activated platelets or shed from stimulated lymphocytes [21,22,23,24]. CD40-CD154 interactions were shown to play a pivotal role in different T-cell-mediated inflammatory disorders [20,21,25,26,27] and disruption of CD40-CD40L interactions proved to be sufficient to prevent the development and progression of several autoimmune diseases [28,29] as well as allograft rejection [21,26].…”
Section: Introductionmentioning
confidence: 99%
“…24 Nevertheless, it may be a partly useful marker in some subjects with high cardiovascular risks, such as unstable plaque 25 or acute coronary syndromes. 9 Large studies performed in the healthy general population have reported that circulating sCD40L is not useful in screening for subclinical atherosclerosis 26 and is poorly associated with known cardiovascular risk factors. 27 Likewise, our findings showed the inverse association between CPT%PDV and sCD40L in some patients, including males and smokers.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several studies demonstrate that plasma C-reactive protein (CRP), adipocytokines and soluble CD40 ligand (sCD40L) act as atherosclerotic biomarkers and are independently associated with cardiovascular events. 7,9,10 Development in ultrasound technology has made it possible to assess blood flow in the distal left anterior descending coronary artery (LAD) with transthoracic Doppler echocardiography (TTE). 11 The cold pressor test (CPT) is one of the methods used to estimate coronary endothelial function or early atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. (3,8,9). CD40L also plays a role in thrombosis by inducing TF expression on endothelial cells and monocytes, operating as a platelet agonist, and stabilizing arterial thrombi (1,3,8,10).…”
mentioning
confidence: 99%